The function of the Roman Army in Southern Arabia Petraea - Castro, Mariana (Archaeopress Roman archaeology, 2018)
This volume provides a fresh perspective on the evolving and diverse functions of the Roman army in Arabia from the creation of the province to the end of the Byzantine period